National security, leaks, and freedom of the press the Pentagon papers fifty years on - Bollinger, Lee C. 1946-; Stone, Geoffrey R. (New York, NY Oxford University Press, 2021)
This chapter principally reviews the development of the law in the United States since the Pentagon Papers decision. It then more briefly addresses three related subjects: the difficulties in assessing the effectiveness of the Pentagon Papers regime in permitting disclosures that benefit public debate more than they harm national security while discouraging leaks that cause more harm than good; how the US legal framework for handling national security information compares to the United Kingdom's; and how technological and institutional changes over the five decades since the Pentagon Papers decision have called into question some of that decision's premises. I.Developments in US Law Since the Pentagon Papers case, the government only rarely has sought to enjoin publication of material-and only once succeeded in winning an injunction on the ground that publication threatened national security. When courts have examined questions of prior restraints, they have consistently looked to the Pentagon Papers decision's reaffirmance of the presumptive unconstitutionality of prior restraints. Since 1971, the government has never sought criminal penalties against the press for merely receiving or publishing classified information. It has, however, brought criminal prosecutions against government employees who leaked classified information to the press without authorization, and it has also sought to prosecute non-media third parties for their role in disseminating information leaked to them by government insiders. The influence of New York Times Co. has been much more limited in these prosecutions. Indeed, in criminal prosecutions brought against leakers, the Pentagon Papers case has often been sidelined as a "prior restraint case," or not mentioned at all. Recently, the government has broken new ground by bringing criminal charges against an organization that some consider to be part of the press-WikiLeaks-alleging that it actively participated in and abetted a leak of classified information. The relevance of New York Times Co. to that situation is uncertain"--
Fighting for balance / Avril Haines -- Crafting a new compact in the public interest : protecting the national security in an era of leaks / Keith B. Alexander and Jamil N. Jaffer -- Leaks of classified information : lessons learned from a lifetime on the inside/ Michael Morell -- Reform and renewal : lessons from Snowden and the 215 program / Lisa O. Monaco -- Government needs to get its own house in order / Richard A. Clarke -- Behind the scenes with the Snowden files : "how the Washington Post and national security officials dealt with conflicts over government secrecy" / Ellen Nakashima -- Let's be practical : a narrow post-publication leak law would better protect the press / Stephen J. Adler and Bruce D. Brown -- What we owe whistleblowers / Jameel Jaffer -- The long, (futile?) Fight for a federal shield law / Judith Miller -- Covering the cyberwars : the press vs the government in a new age of global conflict / David Sanger -- Outlawing leaks / David A. Strauss -- The growth of press freedoms in the United States since 9/11 / Jack Goldsmith -- Edward Snowden, Donald Trump, and the paradox of national security whistleblowing / Allison Stanger -- Information is power : exploring a constitutional right of access / Mary-Rose Papandrea -- Who said what to whom / Cass R. Sunstein -- Leaks in the age of Trump / Louis Michael Seidman the report of the commission, Lee C. Bollinger, Eric Holder, John O. Brennan, Ann Marie Lipinski, Kathleen Carroll, Geoffrey R. Stone, Stephen W. Coll -- Closing statement / Lee C. Bollinger and Geoffrey R. Stone.
Includes bibliographical references and index.
Keywords: Snowden, Edward J. -- 1983-.; Pentagon Papers; Freedom of the press -- Electronic book -- United States; Government and the press -- United States; Security classification (Government documents) -- United States; Government information -- Law and legislation -- United States; Leaks (Disclosure of information) -- History. -- United States; National security -- Law and legislation -- United States; Public records -- Acces control -- United States